Analysis of Academic Burnout Based on School Anxiety with the Mediating Role of Self-Directed Learning in High School Students - Tabar Niarami, Razieh; Eslahi Farshami, Fatemeh; Khazaei, Kamian (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to present a structural model of academic burnout based on school anxiety with the mediating role of self-directed learning among high school students.Methods and Materials: The research was conducted using a descriptive correlational method and structural equations. The statistical population consisted of female high school students enrolled in public high schools (theoretical branch) in Babol during the 2022-2023 academic year, with a total estimated number of 3,254 students based on the Planning Office of the Babol Department of Education. The sample size was estimated at 242 individuals using Cochran's formula (Hafeznia, 2010), and the sampling was conducted using a multi-stage cluster random method. Data were collected using the Academic Burnout Questionnaire (Salmela-Aro & Näätänen, 2005), the Self-Directed Learning Questionnaire (Fisher et al., 2013), and the School Anxiety Questionnaire (Phillips, 1978). For inferential data analysis, structural equation modeling was conducted using PLS software version 4, and multiple regression analysis was performed using SPSS26 software.Findings: The findings indicated that self-directed learning significantly mediates the relationship between school anxiety and academic burnout, with a path coefficient of 0.168. Additionally, the findings showed that among the components of school anxiety, fear of self-expression, test anxiety, and lack of self-confidence have predictive power for academic burnout.Conclusion: It can be concluded that the structural model of academic burnout based on school anxiety with the mediating role of self-directed learning in high school students demonstrated a good fit.